Rethinking education for Sea Nomads through the On–Off School Model: a perspective on holistic and culturally adaptive schooling for the Bajo people in Indonesia - Nurhaliza, Wa Ode Sitti; Sarwoprasodjo, Sarwititi; Fatchiya, Anna; Suharjito, Didik (Frontiers in Communication, 2025)
This perspective presents a culturally grounded model of education for nomadic maritime communities, drawing on the lived experiences of the Bajo people in Wakatobi, Indonesia. Rooted in a sea-based way of life, the Bajo face systemic barriers to formal education due to rigid school structures that do not reflect seasonal mobility or cultural worldviews. The proposed On–Off School Model redefines education as a dynamic and reciprocal process, where formal instruction (“On”) aligns with times of settlement, and community-based experiential learning (“Off”) takes place during sea voyages. This framework is inspired by Indigenous Holistic Education, which integrates four interdependent dimensions: Body, Spirit, Heart, and Mind. From a developmental communication standpoint, the model highlights the importance of listening, co-creating, and honoring local knowledge systems. Rather than imposing top-down interventions, education has become a dialogic practice rooted in empathy, relevance, and respect. This perspective argues that inclusive education must be adaptable, place-based, and culturally affirming, particularly for historically marginalized groups like the Bajo. The On–Off School invites scholars and policymakers to rethink educational equity through the lens of movement, culture, and communication.